Indianapolis the true story of the worst sea disaster in U.S. naval history and the fifty-year fight to exonerate an innocent man - Vincent, Lynn; Vladic, Sara; Lloyd, John Bedford (New York City, NY Simon & Schuster Audio, 2018)
Based on new primary sources and interviews with 108 survivors, Vincent and Vladic reveal the untold stories of the crew left adrift for five days in the Philippine Sea as they battled dehydration, sharks, insanity, and each other; the Army spy who shepherded the bomb aboard Indianapolis; the hidden history of the Top Secret ULTRA program that could have saved the ship; and the survivors' fifty-year fight for justice. In this powerfully emotional account, the USS Indianapolis and its heroic crew come to full, vivid, unforgettable life.
Prologue: The ship -- The kamikaze -- The mission -- The deep -- Trial and scandal -- An innocent man -- Final log entry: August 19, 2017.
Title from container.
Compact discs.
Disc one includes PDF of additional materials.
Read by John Bedford Lloyd.
107327
Keywords: McVay, Charles Butler -- III, -- 1898-1968 -- Trials, litigation, etc; Indianapolis (Cruiser) -- History; United States. -- Navy -- Search and rescue operations -- Pacific Ocean; World War, 1939-1945 -- Naval operations, American; World War, 1939-1945 -- Search and rescue operations -- Pacific Ocean; Shipwrecks -- Pacific Ocean; Military -- History -- Naval; Military -- History -- World War II; Maritime History & Piracy. -- History; Armed Forces -- Search and rescue operations; Military operations, Naval -- American; Search and rescue operations; Audiobooks; History; Trials, litigation, etc